Mechanical characteristics of columnar jointed rock at dam base of Baihetan hydropower station - Yan, Dong-xu; Xu, Wei-ya; Zheng, Wen-tang; Wang, Wei; Shi, An-chi; Wu, Guan-ye (Journal of Central South University of Technology. Science & technology of mining and metallurgy, 2011)
Irregular columnar jointed structure is a primary irregular columnar morphological tensile fracture. In order to study the geometric features of irregular columnar joints and the new problems in geotechnical engineering, hydraulic and hydropower engineering caused by columnar jointed basaltic mass, Voronoi graph from geometry was introduced to simulate the irregular columnar jointed basaltic mass at Baihetan hydraulic station. Discrete element software UDEC was used to simulate the whole process of rigid bearing plate test. Anisotropic constitutive of columnar joints was adopted to analyze the stress diffusion of rock mass at dam base of Baihetan. The results show that, the compaction property and hysteresis effect are well simulated based on discrete element simulation of Voronoi joint structure by UDEC. Four stages of cyclic loading and unloading process are imaged clearly. The results from in situ rigid bearing plate tests are explicated and the stress diffusion rule of anisotropic body is affected by structure surface. The elements in the stress state of 4–5 MPa are the most, about more than 35% of the total. Appropriate constitutive must be proposed to columnar jointed rock mass with different styles. It has important significance to realize the nonlinear mechanical behavior of irregular columnar jointed basaltic mass.